Getting emotional or cognitive on social media? Analyzing renewable energy technologies in Instagram posts. (June 2022) - Vespa, Mariangela; Schweizer-Ries, Petra; Hildebrand, Jan; Kortsch, Timo
Abstract: Renewable energy development is a widely and intensively discussed topic, though it is still unclear which exactly variables may influence people's evaluation of the phenomenon. There is a need to study the general public's knowledge, emotions, and cognitions linked to energy technologies especially in the context of advanced inventions. Social media is a powerful communication tool which has a huge impact on studying public opinions. This study aims to describe linguistic connections through an analysis of 1500 Instagram posts, assuming and interpreting emotional and/or cognitive words. Using a socio-cognitive approach, this research explores the salient words under a set of pre-specified renewable energy technology (RET) hashtags. Building on the appraisal theories of emotions, this research investigates the coexistence of several energy technologies (solar, wind, biomass, and geothermal) and powerlines. The results showed the highest linguistic interconnection between solar and wind energy posts. Furthermore, powerlines were not linguistically connected to the RETs, as they are not included in the schema or not salient when people write posts about renewable energy. Solar, wind, and geothermal posts evoked more emotional and positive emotions than the other RETs and powerlines. Instead, biomass posts had a high frequency of cognitive processes and causal words. Powerline posts were linked to the words of risk, body, health, and biological process showing a great concern for health and perceived threat. These differences in the words used can be a guide to understanding peoples' reactions and communication for each of the energy sources. This study, taking both emotions and cognitions into account, explains different types of considerations towards energy projects.